Pharmacokinetic and nephroprotective benefits of using Schisandra chinensis extracts in a cyclosporine A-based immune-suppressive regime - Lai Q; Wei JB; Mahmoodurrahman M; Zhang CX; Quan SJ; Li TM; Yu Y (Dove Medical Press, 2015)
Qiao Lai,1 Jiabao Wei,1 Mohammed Mahmoodurrahman,2 Chenxue Zhang,1 Shijian Quan,1 Tongming Li,1 Yang Yu11Department of Formulas of Traditional Chinese Medicine, School of Chinese Materia Medica, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 2College of Medicine, Alfaisal University, Riyadh, Saudi ArabiaAbstract: Cyclosporine A (CsA) is a powerful immunosuppressive drug. However, nephrotoxicity resulting from its long-term usage has hampered its prolonged therapeutic usage. Schisandra chinensis extracts (SCE) have previously been used in traditional Chinese medicine and more recently coadministered with Western medicine for the treatment of CsA-induced side effects in the People’s Republic of China. This study aimed to investigate the possible effects of SCE on the pharmacokinetics of CsA in rats and elucidate the potential mechanisms by which it hinders the development of CsA-induced nephrotoxicity. A liquid chromatography/tandem mass spectrometry method was developed and validated for determining the effect of SCE on the pharmacokinetics of CsA. Male Sprague Dawley rats, which were administered with CsA (25 mg/kg/d) alone or in combination with SCE (54 mg/kg/d and 108 mg/kg/d) for 28 days, were used to evaluate the nephroprotective effects of SCE. Our study showed that SCE increased the mean blood concentration of CsA. Furthermore, we found that the concomitant administration of SCE alongside CsA prevented the disruption of catalase activity and reduction in creatinine, urea, renal malondialdehyde, and glutathione peroxidase levels that would have otherwise occurred in the absence of SCE administration. SCE treatment markedly suppressed the expression of 4-hydroxynonenal, Bcl-2-associated X protein, cleaved caspase 3, and autophagy-related protein LC3 A/B. On the other hand, the expression of heme oxygenase-1, nuclear factor erythroid 2-related factor 2 (Nrf2), and P-glycoprotein was enhanced by the very same addition of SCE. SCE was also able to increase the systemic exposure of CsA in rats. The renoprotective effects of SCE were thought to be mediated by its antiapoptotic and antioxidant abilities, which caused the attenuation of CsA-induced autophagic cell death. All in all, these findings suggest the prospective use of SCE as an effective adjunct in a CsA-based immunosuppressive regimen.Keywords: Schisandra chinensis extracts, cyclosporine A, pharmacokinetics, nephroprotective, oxidative stress, apoptosis, autophagy